Balls' in Your Court : a health communication campaign encouraging young men to take charge of their health by practising testicular self-examination - Khong, Faith Qi (2019)
This paper presents Balls’ in Your Court, the first health communication campaign in Singapore that focuses on raising awareness about testicular cancer and Testicular Self- Examination (TSE). Initiated by three final-year undergraduates from the Wee Kim Wee School of Communication and Information at Nanyang Technological University, the campaign aimed to encourage young men in Singapore aged 18 to 30 to practice TSE on a regular basis.